Teaching Vocabulary through Fly Swatter Game (A study conducted at the first grade students of SMP Negeri 03 Paguyaman) - Tiwi Aprilia Samwan; Rasuna Rasid Talib; Rahmawaty Mamu (Jambura Journal of English Teaching and Literature, 2021)
Vocabulary is one of the important components to master all of language skills. It has strategic positions in education and teaching. Fly Swatter game is an interesting technique in teaching and learning that makes the students can learn through playing. Therefore, this study aims to find out whether the game of Fly swatter can significantly enhance the student’s vocabulary mastery or not. It focuses only on mastering adjective and noun class. The sample of this research was the students of Paguyaman Junior high school at VII B class. Further, this study is using quantitative analysis, in investigating the student’s improvement in mastering vocabulary, the researcher give test to the students which consist of 40 numbers, which divided into 20 tests each for noun and adjective. To analyze the student’s improvement, the researcher use pre experimental design, there are three steps used that are pre test, treatment, and post test. The finding reveals that there is significance improvement on the result of pre test and post test. It was from 40% which categorized in poor level increase into 95% which categorize in excellent level, with the total increases was around 55% . Furthermore, it was proved by the result of hypothesis verification, it is found that T count = 19, 44 at the level of significance (a = 0, 05) and degree of freedom (df ) = 19-1=18. Then, it is found that T table = 2,101, it can be concluded that fly swatter game can increase students ability in vocabulary, because based on the criteria above shows that T count is more than T table 19, 44 ≥ 2,101.